Estudo do crescimento, estabilidade física, química e termogravimétrica com rações para camarão marinho Litopenaues vannamei - Capistrano Sobrinho, David (2011)
The Aquaculture has been a fast developed in recent years and the shrimp farming is the best business and has been a great growing, but the feed is consider the higher cost of production and the major source of pollution of shrimp farms. In this context it is need look for a feed with quality and a new ingredient. The aim of the present study was to analysis different commercial feed and another elaborate feed about the physical and chemical stability. We performed the study for 50 days. We used 35 tanks and the density was of five shrimp per aquarium. The shrimp had a feed different. The physic-chemical parameters were monitoring. We observed the weight gain of shrimp growth rates, growth rate and specific growth rate. It was also observed in lleaching of nutrients at time intervals, 04, 08 and 12 hours. The proximate food composition in feed analyses has required the requirements nutritional. The survival rate during cultivation was 74 to 88%, where shrimp fed the diet R6 had the highest growth rates. The physical stability of the diets, R1 to R7, showed significant differences between them, ranging from 34 to 141 minutes for its degradation. As the nutrient loss was gradual, with the highest was evident with the R4. The thermo gravimetric profile of the diets, R1 to R7, had similar characteristics, indicating three stages of thermal decomposition.